Preparation method and application of bromine-doped sodium vanadium fluorophosphate oxide@carbon composite material

CN123017927APending Publication Date: 2026-10-30GUANGDONG UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611196612.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-07
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

其中,多数离子掺杂研究主要集中于过渡金属钒位和钠位掺杂,以改善材料的电化学性能,但这种策略存在局限性:钒中心对Na+扩散行为的影响需通过与其配位的悬垂F-或O2-间接传递,因此对Na+扩散速率的直接调控作用有限;而钠位掺杂则因掺杂离子占据钠活性位点,在扩宽离子通道的同时往往需要牺牲部分可逆容量和长循环结构稳定性为代价,且对表面氧活性及界面副反应的调控能力不足

Benefits of technology

本发明以乙酰丙酮氧钒为钒源、氟化钠为钠源和氟源、磷酸二氢铵为磷酸根源,并以十六烷基三甲基溴化铵兼作掺杂剂和碳源。将上述原料混合后,经水热反应制得前驱体,再于惰性气氛下高温煅烧,最终获得溴掺杂氟磷酸氧钒钠/氮碳复合材料(Na3V2O1.85Br0.15(PO4)2F@NC)。通过对XRD数据进行精修,确认Br离子占据O2位点,且获得良好的精修因子,证实了Br在O2位的成功掺杂。将该复合材料用作钠离子电池正极时,电池展现出优异的倍率性能和稳定的循环性能,同时在长循环过程中保持较高的结构稳定性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123017927A_ABST
    Figure CN123017927A_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of sodium ion battery electrode materials, and particularly relates to a preparation method and application of bromine-doped sodium fluorophosphate oxyvanadate@carbon composite material. A hydrothermal-assisted calcination method with low cost, simple operation and easy scale production is adopted, and hexadecyl trimethyl ammonium bromide is introduced as a double-function reagent to realize in-situ doping of bromine element and carbon coating in one step, and finally obtain bromine-doped sodium fluorophosphate oxyvanadate / nitrogen-carbon composite material. On the one hand, appropriate bromine element doping can replace part of oxygen sites in the material in-situ, improve electronic conductivity and ion diffusion kinetics; on the other hand, the carbon coating layer can further improve the charge transport capacity. Therefore, due to the synergistic effect of bromine doping and carbon coating, the composite material as a positive electrode of sodium ion battery can not only give the battery excellent rate performance, but also enable it to maintain high structural stability during long cycle process, thereby obtaining excellent cycle life and electrochemical performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of sodium-ion battery electrode material technology, specifically relating to a method for preparing and applying a bromine-doped sodium vanadium fluoride phosphate@carbon composite material. Background Technology

[0002] Against the backdrop of global efforts to address climate change and advance energy transition, building a clean and low-carbon energy system has become a general consensus. Electrochemical energy storage, as a crucial supporting technology for this system, is experiencing significant development opportunities. Lithium-ion batteries, with their high energy density and mature industrial chain, have already achieved a dominant position in consumer electronics, electric vehicles, and energy storage, powerfully driving the development of green mobility. However, with the rapid development of clean energy and electrification, the scarcity and uneven distribution of lithium resources are becoming increasingly prominent, leading to drastic fluctuations in raw material prices and rising costs. Furthermore, the performance degradation of lithium-ion batteries under extreme temperatures and the risk of thermal runaway also limit their application in large-scale energy storage scenarios.

[0003] Faced with the constraints of lithium resources, the development of next-generation rechargeable battery systems that are abundant, inexpensive, and safer has become an urgent need. Sodium and lithium belong to Group I and share similar physicochemical properties and a "rocking chair" energy storage mechanism, thus sodium-ion batteries have attracted widespread attention from academia and industry. Sodium resources are extremely abundant, evenly distributed globally, and have low extraction costs. Furthermore, sodium-ion batteries exhibit unique advantages in low-temperature discharge performance, over-discharge safety, and current collector selection (both positive and negative electrodes can use inexpensive aluminum foil instead of copper foil), thus being recognized as one of the most promising alternatives in large-scale energy storage and low-to-medium speed electric transportation.

[0004] In sodium-ion battery cathode materials, polyanionic compounds have attracted much attention due to their stable three-dimensional framework structure and excellent thermal stability. Among them, sodium vanadium fluorophosphate (Na3(VO)2(PO4)2F) is a typical polyanionic cathode material, exhibiting high operating voltage, good cycle stability, and high theoretical specific capacity. This type of material achieves this by introducing the highly electronegative F... - Or O 2- This can effectively increase the potential of transition metal redox pairs, thereby obtaining a higher operating voltage. However, the introduction of highly electronegative ions will affect the Na+ in the Na layer. + Electrostatic binding occurs, leading to Na + The insertion / extraction kinetics become slow. This is the main reason for the poor rate performance, large plateau polarization, and low capacity retention of sodium vanadium fluorophosphate over long cycles, which seriously hinders their practical application.

[0005] Currently, the main modification methods for addressing the above problems are carbon coating and ion doping. Ion doping can be further divided into sodium-site doping, vanadium-site doping, and anion doping. Most ion doping research focuses on vanadium and sodium sites in transition metals to improve the electrochemical performance of materials, but this strategy has limitations: the vanadium center is susceptible to Na+ doping. + The effects of diffusion behavior require the coordination of its dangling F - Or O 2- Indirect transmission, therefore for Na + Direct modulation of diffusion rate has limited effect; while sodium doping, due to the dopant ions occupying sodium active sites, often sacrifices some reversible capacity and long-cycle structural stability while widening ion channels, and its ability to regulate surface oxygen activity and interfacial side reactions is insufficient. In contrast, anion doping, by constructing a hybrid anion framework, can significantly improve the intrinsic electronic conductivity and sodium ion transport kinetics of the material while effectively mitigating interfacial side reactions under high voltage, thereby achieving a comprehensive optimization of high energy density and long-cycle stability. However, existing anion doping strategies still face many challenges in terms of dopant element selection, precise control of dopant concentration, and multi-anion synergistic regulation mechanisms, and further improvements are needed to meet practical application requirements. Summary of the Invention

[0006] To overcome the shortcomings of the prior art, the present invention provides a bromine-doped sodium vanadium fluorophosphate@carbon composite material (Na3V2O). 1.85 Br 0.15 The preparation method of (PO4)2F@NC employs a simple, mild, environmentally friendly, and easily scalable conventional hydrothermal assisted calcination method. By adding the modifier hexadecyltrimethylammonium bromide (CTAB), Br element is doped into the suspended oxygen sites (O2 sites) of sodium vanadium fluorophosphate in one step, and a highly conductive carbon composite network is simultaneously constructed. This allows the composite material to achieve excellent rate performance and stable cycle performance when used as a cathode material in sodium-ion batteries, while ensuring structural stability during long-term cycling.

[0007] To achieve the above objectives, the technical solution adopted by the present invention is as follows: The first aspect of this invention provides a method for preparing a bromine-doped sodium vanadium fluorophosphate@carbon composite material, the method comprising the following steps: S1. Vanadium acetylacetonate solution was prepared by dissolving vanadium acetylacetonate in ethanol. A mixed solution was prepared by dissolving ammonium dihydrogen phosphate, sodium fluoride and hexadecyltrimethylammonium bromide in water. The two solutions were combined and subjected to a hydrothermal reaction. After the reaction, the precursor was obtained by washing and drying. S2. The reaction precursor from step S1 is placed in an inert gas atmosphere for high-temperature sintering to obtain the bromine-doped sodium vanadium fluorophosphate@carbon composite material (Na3V2O). 1.85 Br 0.15 (PO4)2F@NC).

[0008] This invention effectively solves the problems of high energy consumption, cumbersome process, and low safety in traditional synthesis processes using a conventional hydrothermal method, and features simple process, mild conditions, and environmental friendliness. Furthermore, by adding hexadecyltrimethylammonium bromide, bromine doping and carbon coating are achieved in one step, improving the electronic conductivity of the material.

[0009] Preferably, the molar ratio of vanadium acetylacetonate, ammonium dihydrogen phosphate, sodium fluoride and hexadecyltrimethylammonium bromide is 0.5-2:1-2:1-3:0.3-2.

[0010] Preferably, the hydrothermal reaction is carried out at a temperature of 110-150°C for 7-13 hours.

[0011] Preferably, the washing involves centrifuging the hydrothermal reaction product with water and ethanol respectively to remove impurities and collect the precipitate.

[0012] Preferably, the high-temperature sintering temperature is 500-700℃ and the time is 6-8h.

[0013] Preferably, the inert gas is argon or nitrogen.

[0014] Preferably, the drying is performed at 60-80 °C for 10-12 h.

[0015] A second aspect of the present invention also provides a bromine-doped sodium vanadium fluorophosphate@carbon composite material, which is prepared by the preparation method described in the first aspect.

[0016] Preferably, the particle size of the bromine-doped sodium vanadium fluorophosphate@carbon composite material is 30-50 nm.

[0017] This invention combines three modification methods: surface carbon coating modification, morphology modification, and anion doping modification. A hydrothermal method is used to prepare NVOPF materials with small particle size (30-50 nm) and uniform particle size distribution. Subsequently, the NVOPF is coated with a carbon composite material to improve interparticle conductivity and stabilize the material morphology. Bromine ions are used to dope the pendant oxygen sites of sodium fluorophosphate, further enhancing the intrinsic electronic and ionic conductivity of the NVOPF material. Therefore, the bromine-doped sodium fluorophosphate@carbon composite material Na3V2O1.85Br0.15(PO4)2F@NC prepared by this invention, when used as a cathode material for sodium-ion batteries, can enable the battery to achieve excellent rate performance and stable cycle performance, while ensuring structural stability during long-term cycling.

[0018] The third aspect of the present invention also provides the application of the bromine-doped sodium vanadium fluoride phosphate@carbon composite material described in the second aspect as a cathode material in the preparation of sodium-ion batteries.

[0019] Preferably, when preparing the positive electrode of a sodium-ion battery using the aforementioned bromine-doped sodium fluorophosphate@carbon composite material, the bromine-doped sodium fluorophosphate@carbon composite material is mixed with a conductive agent (such as Ketjen Black) and a binder (sodium carboxymethyl cellulose) to prepare a slurry. The mass ratio of the bromine-doped sodium fluorophosphate@carbon composite material, the conductive agent, and the binder is 6-8:1.2-2.8:0.4-1.6.

[0020] Compared with the prior art, the beneficial effects of the present invention are: This invention uses vanadium oxyacetylacetonate as the vanadium source, sodium fluoride as the sodium and fluorine source, and ammonium dihydrogen phosphate as the phosphate source, with hexadecyltrimethylammonium bromide serving as both a dopant and a carbon source. The above raw materials are mixed and subjected to a hydrothermal reaction to obtain a precursor, which is then calcined at high temperature under an inert atmosphere to finally obtain a bromine-doped sodium vanadium oxyacetylacetonate / nitrogen-carbon composite material (Na3V2O). 1.85 Br 0.15 (PO4)2F@NC). Refinement of XRD data confirmed that Br ions occupy the O2 sites, achieving a good refinement factor, thus verifying the successful doping of Br at the O2 sites. When this composite material was used as the cathode of a sodium-ion battery, the battery exhibited excellent rate performance and stable cycling performance, while maintaining high structural stability during long-term cycling.

[0021] This invention employs a conventional hydrothermal assisted calcination process that is low-cost and easy to scale up, significantly shortening the reaction time and improving production efficiency. Furthermore, by combining NVOPF with nitrogen-carbon materials exhibiting high electronic conductivity and incorporating an O2-site halogen doping strategy, electronic conductivity is synergistically enhanced at both the material surface and bulk levels, thereby obtaining a nitrogen-carbon composite sodium-ion battery cathode material that combines high-rate performance with long-cycle stability. Attached Figure Description

[0022] Figure 1 Na3V2O 1.85 Br 0.15 The X-ray diffraction pattern of (PO4)2F@NC (top) and the refined schematic diagram (bottom).

[0023] Figure 2 Na3V2O 1.85 Br 0.15 Scanning electron microscope image of (PO4)2F@NC.

[0024] Figure 3 Na3V2O 1.85 Br 0.15 Transmission electron microscope image of (PO4)2F@NC.

[0025] Figure 4 Na3V2O 1.85 Br 0.15 (PO4)2F@NC as the positive electrode material of sodium-ion batteries: charge and discharge curves at different current densities.

[0026] Figure 5 Na3V2O 1.85 Br 0.15 Rate performance of (PO4)2F@NC and sodium vanadium fluorophosphate as cathode materials for sodium-ion batteries at current densities of 1-100C.

[0027] Figure 6 Na3V2O 1.85 Br 0.15 (PO4)2F@NC as a cathode material for sodium-ion batteries: Cyclic performance at a current density of 1C.

[0028] Figure 7 Na3V2O 1.85 Br 0.15 (PO4)2F@NC as a cathode material for sodium-ion batteries: Cyclic performance at a current density of 20C.

[0029] Figure 8 Na3V2O 1.85 Br 0.15 Scanning electron microscope (SEM) image of (PO4)2F@NC as a cathode material for sodium-ion batteries after 200 cycles at a current density of 1C.

[0030] Figure 9 Na3V2O 1.85 Br 0.15X-ray diffraction pattern of (PO4)2F@NC as the cathode material of sodium-ion battery after 200 cycles at a current density of 1C.

[0031] Figure 10 The image shows the X-ray diffraction pattern of sodium vanadium fluorophosphate.

[0032] Figure 11 This is a scanning electron microscope image of sodium vanadium fluorophosphate.

[0033] Figure 12 Charge-discharge curves of sodium vanadium fluorophosphate as a cathode material in sodium-ion batteries at different current densities.

[0034] Figure 13 The graph shows the cycling performance of sodium vanadium fluorophosphate as a cathode material in sodium-ion batteries at a current density of 1C.

[0035] Figure 14 The graph shows the cycling performance of sodium vanadium fluorophosphate as a cathode material in sodium-ion batteries at a current density of 20C.

[0036] Figure 15 Scanning electron microscope (SEM) image of sodium vanadium fluorophosphate as a cathode material in sodium-ion batteries after 200 cycles at a current density of 1C.

[0037] Figure 16 The X-ray diffraction pattern of sodium vanadium fluorophosphate as a cathode material in sodium-ion batteries after 200 cycles at a current density of 1C.

[0038] Figure 17 The X-ray diffraction pattern of chlorine-doped sodium vanadium fluorophosphate (top image) and the refined schematic diagram (bottom image).

[0039] Figure 18 This is a scanning electron microscope image of chlorine-doped sodium vanadium fluorophosphate.

[0040] Figure 19 The graph shows the rate performance of chlorine-doped sodium fluorophosphate as a cathode material for sodium-ion batteries at current densities of 1-100C.

[0041] Figure 20 Charge-discharge curves of chlorine-doped sodium vanadium fluoride phosphate as a cathode material in sodium-ion batteries at different current densities.

[0042] Figure 21 The figure shows the cycling performance of sodium vanadium fluorophosphate as a cathode material in a sodium-ion battery at a current density of 1C.

[0043] Figure 22 The graph shows the cycling performance of chlorine-doped sodium vanadium fluoride phosphate as a cathode material in a sodium-ion battery at a current density of 20C. Detailed Implementation

[0044] The specific embodiments of the present invention will be further described below. It should be noted that these descriptions are for the purpose of aiding understanding the present invention, but do not constitute a limitation thereof. Furthermore, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0045] Unless otherwise specified, the experimental methods used in the following embodiments are conventional methods, and the experimental materials used in the following embodiments are all available through conventional commercial channels.

[0046] This invention provides a bromine-doped sodium vanadium fluorophosphate@carbon composite material (Na3V2O) 1.85 Br 0.15 The preparation method of (PO4)2F@NC is as follows: vanadium source, sodium fluoride as sodium source and fluorine source, ammonium dihydrogen phosphate as phosphate source, and hexadecyltrimethylammonium bromide as both dopant and carbon source are used to prepare the product through hydrothermal reaction and high-temperature calcination in an inert atmosphere.

[0047] This invention employs a low-cost, simple, and easily scalable hydrothermal calcination method. By introducing hexadecyltrimethylammonium bromide as a dual-functional reagent, it achieves in-situ bromine doping and carbon coating in one step, effectively simplifying the operation steps of traditional processes and significantly improving production efficiency. Regarding microstructure and performance regulation, appropriate bromine doping can in-situ replace some oxygen sites in the material, thereby effectively reducing the activation energy of sodium ion migration and improving electronic conductivity and ion diffusion kinetics. Simultaneously, the uniform and dense carbon coating layer not only inhibits excessive particle growth and aggregation during synthesis but also enhances electronic contact between particles, further improving charge transport capabilities. In summary, thanks to the synergistic effect of bromine doping and carbon coating, using this composite material as the cathode for sodium-ion batteries not only endows the battery with excellent rate performance but also maintains high structural stability during long cycles, resulting in superior cycle life and electrochemical performance.

[0048] To fully and clearly present the technical solution and significant advantages of the present invention, the present invention will be described in detail below with reference to specific embodiments.

[0049] Example 1: Preparation and performance testing of bromine-doped sodium vanadium fluorophosphate@carbon composite material 1. Preparation of bromine-doped sodium vanadium fluorophosphate@carbon composite material (1) Dissolve 530.3 mg of acetylacetonate vanadyl in 32 mL of anhydrous ethanol and stir at 200 r / min for 20 min at room temperature to obtain a uniform acetylacetonate vanadyl solution. (2) Dissolve 345.1 mg ammonium dihydrogen phosphate, 140.2 mg sodium fluoride and 524.3 mg cetyltrimethylammonium bromide in 40 mL of deionized water and stir at 200 r / min for 20 min at room temperature to obtain a mixed solution; (3) Mix the vanadium acetylacetone solution obtained in step (1) and the mixed solution obtained in step (2), and continue to stir at 200 r / min for 10 min at room temperature to obtain a premixed solution; (4) The premixed solution containing vanadium acetylacetonate, ammonium dihydrogen phosphate, sodium fluoride and hexadecyltrimethylammonium bromide obtained in step (3) was hydrothermally reacted at 130°C for 10 h; (5) The product of the hydrothermal reaction was washed three times each with deionized water and anhydrous ethanol at a speed of 8000 r / min to remove impurities. The centrifuged precipitate was dried at 60℃ for 10 h to obtain the reaction precursor. (6) The reaction precursor is placed in a tube furnace and heat-treated at 600°C for 7 hours under an argon atmosphere to obtain the bromine-doped sodium vanadium fluoride phosphate@carbon composite material Na3V2O. 1.85 Br 0.15 (PO4)2F@NC.

[0050] like Figure 1 As shown, the Na3V2O prepared in this embodiment 1.85 Br 0.15 In the X-ray diffraction (XRD) pattern of the (PO4)2F@NC sample, the positions and relative intensities of all diffraction peaks were in excellent agreement with the standard card, and no impurity peaks were observed. Furthermore, the sharp peak shapes indicated high purity and good crystallinity of the material. Further Rietveld refinement analysis of the XRD data showed that when Br... - When the O2 site is occupied, the optimal refinement factor can be obtained, thus confirming that the Br ion has been successfully doped into the O2 site.

[0051] In terms of microscopic morphology, such as Figure 2 As shown, the material exhibits uniform particle size, with a particle size distribution between 40 and 50 nm. This nanoscale size helps to shorten the diffusion path of sodium ions, thereby improving the material's kinetic properties. Furthermore, transmission electron microscopy (TEM) images clearly show... Figure 3 The material particles are coated with a distinct disordered carbon layer, which not only confirms the successful construction of the NC (nitrogen-doped carbon) coating layer, but also shows that the carbon layer can effectively improve the surface electronic conductivity of the material.

[0052] 2. The Na3V2O obtained in this embodiment 1.85 Br 0.15(PO4)2F@NC is used as a cathode material in sodium-ion batteries. The specific implementation method is as follows: The above Na3V2O 1.85 Br 0.15 (PO4)2F@NC cathode material, Ketjen Black, and sodium carboxymethyl cellulose (CMC-Na) were ground and mixed at a mass ratio of 7:2:1. After adding an appropriate amount of deionized water, grinding continued to obtain a uniform and fine slurry (solid content approximately 65%). This slurry was then uniformly coated onto carbon-coated aluminum foil and dried in a 60℃ oven for 12 hours. After drying, the electrode was cut into 12mm diameter discs. Using the resulting carbon-coated aluminum foil discs loaded with active material as the positive electrode and metallic sodium as the negative electrode, coin cells were assembled and charged / discharge tested within a voltage window of 2.5-4.3 V.

[0053] The Na3V2O prepared in this embodiment 1.85 Br 0.15 The rate performance of (PO4)2F@NC and the original sodium vanadium fluorophosphate was tested at current densities of 1, 2, 5, 10, 20, 30, 50, 80, and 100 C. Figure 4 and 5 As shown, Na3V2O 1.85 Br 0.15 The discharge specific capacities of (PO4)2F@NC at these current densities were 121.3, 120.7, 118.3, 115.7, 112.1, 108.8, 102.9, 92.5, and 85.9 mAh·g, respectively. -1 When the current density returns to 1C, its discharge specific capacity can still reach 121.3 mAh·g. -1 The original sodium vanadium fluorophosphate exhibited excellent rate performance, retaining 100% of its initial 1C capacity. In contrast, the original sodium vanadium fluorophosphate showed discharge specific capacities of only 117.4, 112.9, 106.6, 101.1, 94.6, 90.9, 84.9, 75.1, and 65.0 mAh·g at the same current density. -1 The concentration was significantly lower than that of the Br-doped sample, which fully confirms that Br... - The effectiveness of doping in improving the rate performance of materials.

[0054] Meanwhile, the Na3V2O prepared in this embodiment 1.85 Br 0.15 The cycle performance of the (PO4)2F@NC cathode material at 1C and 20C was tested. Figure 6 and Figure 7 As shown, at a 1C current density, the battery's first-cycle discharge specific capacity is 122.6 mAh·g. -1 It can still provide 121.8 mAh·g after 100 cycles.-1 The battery exhibits a high discharge specific capacity and a capacity retention rate of 99.3%, demonstrating highly stable cycle performance. Even more remarkably, after 90,000 cycles at a high current density of 20C, the battery still maintains a capacity of 62.1 mAh·g⁻¹. -1 Its discharge specific capacity exhibits an extremely long cycle life.

[0055] To investigate the underlying reasons for its excellent cycling stability, the Na3V2O was subjected to 200 cycles at 1C. 1.85 Br 0.15 The (PO4)2F@NC electrode was characterized by SEM and XRD, respectively. Figure 8 and Figure 9 As shown, the morphology of the material particles remained intact after cycling, with no obvious pulverization or cracking. Simultaneously, the positions and relative intensities of the diffraction peaks in the XRD pattern were essentially consistent with those before cycling, and no new impurity phase peaks were observed, indicating that the crystal structure of the material remained highly stable during long-term cycling. This result fully demonstrates that Br... - The synergistic effect of doping and nitrogen-doped carbon coating can effectively stabilize the bulk structure of the material and suppress interfacial side reactions, thereby endowing the material with ultra-stable cycling characteristics.

[0056] Comparative Example 1: Preparation and Performance Testing of Sodium Vanadium Fluorophosphate 1. Preparation of sodium vanadium fluorophosphate material (1) Dissolve 530.3 mg of acetylacetonate vanadyl in 32 mL of anhydrous ethanol and stir at 200 r / min for 20 min at room temperature to obtain a uniform acetylacetonate vanadyl solution. (2) Dissolve 345.1 mg ammonium dihydrogen phosphate and 140.2 mg sodium fluoride in 40 mL of deionized water and stir at 200 r / min for 20 min at room temperature to obtain a mixed solution; (3) Mix the acetylacetone vanadium oxide solution obtained in step (1) and the mixed solution obtained in step (2), and continue to stir at 200 r / min for 10 min at room temperature to obtain a premixed solution containing acetylacetone vanadium oxide, ammonium dihydrogen phosphate and sodium fluoride. (4) The premixed solution containing vanadium acetylacetonate, ammonium dihydrogen phosphate and sodium fluoride obtained in step (3) was hydrothermally reacted at 130°C for 1 h; (5) The product of the hydrothermal reaction was washed three times each with deionized water and anhydrous ethanol at a speed of 8000 r / min to remove impurities. The centrifuged precipitate was dried at 60℃ for 10 h to obtain the reaction precursor. (6) The reaction precursor is placed in a tube furnace and heat-treated at 600°C for 7 hours under an argon atmosphere to obtain sodium vanadium fluorophosphate material.

[0057] like Figure 10 As shown, the diffraction peak positions and relative intensities of its XRD pattern are in good agreement with the standard card, with no other impurities and sharp peak shapes, indicating that the material also has high purity and good crystallinity. However, from Figure 11 The SEM images show that the prepared sodium vanadium fluorophosphate particles are approximately 30-60 nm in size, but the particle size distribution is uneven and obvious agglomeration occurs. This uneven particle agglomeration not only prolongs the diffusion path of sodium ions, but also reduces the contact area between the active material and the conductive agent and electrolyte, which is not conducive to fully releasing its theoretical capacity and achieving long-term cycling stability.

[0058] 2. The obtained sodium vanadium fluorophosphate is used as a positive electrode material in sodium-ion batteries. The specific implementation method is as follows: For comparison, the aforementioned sodium vanadium fluorophosphate cathode material was ground and mixed with Ketjen Black and sodium carboxymethyl cellulose (CMC-Na) at a mass ratio of 7:2:1. After adding an appropriate amount of deionized water, grinding was continued to obtain a uniform and fine slurry (solid content approximately 65%). The slurry was then uniformly coated onto carbon-coated aluminum foil and dried in an oven at 60°C for 12 hours. After drying, the electrode was cut into 12mm diameter discs. A coin cell was then assembled using the carbon-coated aluminum foil discs loaded with active material as the positive electrode and metallic sodium as the negative electrode. Charge-discharge tests were conducted within a voltage window of 2.5–4.3 V to evaluate its electrochemical performance.

[0059] The rate performance of sodium vanadium fluorophosphate was evaluated using charge-discharge curves at different current densities. Figure 12 As shown, with the gradual increase of current density, the electrochemical polarization of the material intensifies significantly, the charging voltage plateau continuously rises, while the discharging voltage plateau continuously declines; when the current density increases to 100 C, the voltage plateau in the charge-discharge curve almost completely disappears. This phenomenon indicates that the electrochemical kinetics of this material are severely limited at high rates, and ion and electron transport cannot meet the demands of rapid reactions in time, thus leading to a sharp increase in polarization and a significant decrease in reversible capacity and energy efficiency. This further highlights the important role of Br doping and carbon coating modification in improving the rate performance of the material.

[0060] The cycling performance of the prepared sodium vanadium fluorophosphate as a cathode material for sodium-ion batteries was tested at 1C and 20C. Figure 13 As shown, at a 1C current density, the battery's first-cycle discharge specific capacity is 115.5 mAh·g. -1 After 100 cycles, the capacity retention was 97.6%, indicating acceptable cycle stability, but slightly inferior to the Br-doped material. At a high current density of 20C, the original material could not complete 20,000 cycles. Figure 14Compared to the previous performance of the modified material, which achieved a stable cycle life of 90,000 cycles at 20°C, its cycle life is significantly insufficient, revealing severe structural degradation at high rates.

[0061] The original sodium vanadium fluorophosphate electrode after 200 cycles at 1C was characterized by SEM and XRD. Figure 15 As shown, numerous cracks appeared on the surface of the electrode material after cycling; simultaneously, the XRD pattern ( Figure 16 The diffraction peaks showed a significant decrease in intensity and a marked broadening in shape, indicating a severe decline in the material's crystallinity. This dual destruction of morphology and structure makes it difficult for the material to effectively buffer volumetric strain and suppress interfacial side reactions during repeated sodium ion insertion / extraction processes, resulting in gradual pulverization of the structure and long-range cycling performance far inferior to the modified material in Example 1.

[0062] Comparative Example 2: Preparation and Performance Testing of Chlorine-Doped Sodium Vanadium Fluorophosphate Cathode Material 1. Preparation of chlorine-doped sodium vanadium fluorophosphate cathode material (1) Dissolve 530.3 mg of acetylacetonate vanadyl in 32 mL of anhydrous ethanol and stir at 200 r / min for 20 min at room temperature to obtain a uniform acetylacetonate vanadyl solution. (2) Dissolve 345.1 mg ammonium dihydrogen phosphate, 140.2 mg sodium fluoride and 23.8 mg sodium chloride in 40 mL of deionized water and stir at 200 r / min for 20 min at room temperature to obtain a mixed solution; (3) Mix the vanadium acetylacetone solution obtained in step (1) and the mixed solution obtained in step (2), and continue to stir at 200 r / min for 10 min at room temperature to obtain a premixed solution; (4) The premixed solution containing vanadium acetylacetonate, ammonium dihydrogen phosphate, sodium fluoride and sodium chloride obtained in step (3) was hydrothermally reacted at 130°C for 10 h; (5) The product of the hydrothermal reaction was washed three times each with deionized water and anhydrous ethanol at a speed of 8000 r / min to remove impurities. The centrifuged precipitate was dried at 60℃ for 10 h to obtain the reaction precursor. (6) The reaction precursor is placed in a tube furnace and heat-treated at 600°C for 7 hours under an argon atmosphere to obtain chlorine-doped sodium fluorophosphate cathode material.

[0063] like Figure 17As shown, the X-ray diffraction pattern of the chlorine-doped sodium vanadium fluorophosphate cathode material prepared in this embodiment shows peak positions and intensities corresponding to the standard card, with no other impurity peaks and sharp peak shapes, indicating good purity and crystallinity of the material. Furthermore, refinement of its XRD data using Fullprof revealed that Cl ion doping at the O2 site yielded a good refinement factor, indicating successful Cl doping. Figure 18 As shown, the particle size of the chlorine-doped sodium vanadium fluorophosphate cathode material prepared in this embodiment is 40-50 nm.

[0064] 2. The chlorine-doped sodium vanadium fluorophosphate obtained in Comparative Example 2 was used as a positive electrode material in a sodium-ion battery. The specific implementation method is as follows: The aforementioned chlorine-doped sodium vanadium fluorophosphate cathode material, Ketjen black, and sodium carboxymethyl cellulose (CMC-Na) were ground and mixed at a mass ratio of 7:2:1. After adding an appropriate amount of deionized water, grinding continued to obtain a uniform and fine slurry (solid content approximately 65%). This slurry was then uniformly coated onto carbon-coated aluminum foil and dried in a 60°C oven for 12 hours. After drying, the electrode was cut into 12mm diameter discs. Using the resulting carbon-coated aluminum foil discs loaded with active material as the positive electrode and metallic sodium as the negative electrode, coin cells were assembled and charged-discharge tests were conducted within a voltage window of 2.5–4.3 V.

[0065] like Figure 19 and Figure 20 As shown, the chlorine-doped sodium vanadium fluorophosphate cathode material exhibits a characteristic charge-discharge voltage plateau at 1-100 C and can output an effective reversible specific capacity. Compared with the bromine-doped sodium vanadium fluorophosphate composite material, its capacity decay rate during cycling is significantly faster, indicating that chlorine doping has a relatively limited effect on maintaining the long-term structural stability of the material.

[0066] like Figure 21 As shown, the chlorine-doped sodium vanadium fluorophosphate cathode material exhibits excellent cycle stability at 1 C, maintaining a stable discharge specific capacity and a coulombic efficiency consistently close to 100%. In contrast, Figure 22 The results show that its cycling performance deteriorates significantly at ultra-high rates of 20 C, and its capacity decreases sharply after 15,000 cycles. This may be due to the increased polarization and the accumulation of material structural strain at high rates.

[0067] In summary, this invention employs a hydrothermal assisted calcination method that is fast-responding, low-cost, and easily scalable to achieve Br at the O2 site. - By precisely doping the nitrogen-doped carbon (NC) layer with high electronic conductivity, Na3V2O was successfully prepared. 1.85 Br 0.15(PO4)2F@NC composite material. The synergistic effect of Br doping and NC coating not only significantly improves the electronic conductivity of the material and shortens the sodium ion diffusion path, but also effectively stabilizes the crystal structure and inhibits particle pulverization and structural degradation during cycling. Thanks to this, this composite material, as a cathode material for sodium-ion batteries, exhibits both high rate capability and ultra-long cycle stability, demonstrating significant advantages as a high-performance sodium-ion battery cathode material.

[0068] The embodiments of the present invention have been described in detail above, but the present invention is not limited to the described embodiments. For those skilled in the art, various changes, modifications, substitutions, and variations can be made to these embodiments without departing from the principles and spirit of the present invention, and these variations still fall within the protection scope of the present invention.

Claims

1. A method for preparing a bromine-doped sodium vanadium fluorophosphate@carbon composite material, characterized in that, Includes the following steps: S1. Vanadium acetylacetonate solution was prepared by dissolving vanadium acetylacetonate in ethanol. A mixed solution was prepared by dissolving ammonium dihydrogen phosphate, sodium fluoride and hexadecyltrimethylammonium bromide in water. The two solutions were combined and subjected to a hydrothermal reaction. After the reaction, the precursor was obtained by washing and drying. S2. The reaction precursor from step S1 is placed in an inert gas atmosphere and sintered at high temperature to obtain bromine-doped sodium vanadium fluorophosphate@carbon composite material.

2. The method for preparing a bromine-doped sodium vanadium fluorophosphate@carbon composite material according to claim 1, characterized in that, The molar ratio of vanadium acetylacetonate, ammonium dihydrogen phosphate, sodium fluoride and hexadecyltrimethylammonium bromide is 0.5-2:1-2:1-3:0.3-2.

3. The method for preparing a bromine-doped sodium vanadium fluorophosphate@carbon composite material according to claim 1, characterized in that, The hydrothermal reaction is carried out at a temperature of 110-150℃ for 7-13 hours.

4. The method for preparing a bromine-doped sodium vanadium fluorophosphate@carbon composite material according to claim 1, characterized in that, The washing process involves centrifuging the hydrothermal reaction product with water and ethanol respectively to remove impurities and collect the precipitate.

5. The method for preparing a bromine-doped sodium vanadium fluorophosphate@carbon composite material according to claim 1, characterized in that, The high-temperature sintering temperature is 500-700℃, and the time is 6-8h.

6. The method for preparing a bromine-doped sodium vanadium fluorophosphate@carbon composite material according to claim 1, characterized in that, The inert gas is argon or nitrogen.

7. The method for preparing a bromine-doped sodium vanadium fluorophosphate@carbon composite material according to claim 1, characterized in that, The drying process involves drying at 60-80℃ for 10-12 hours.

8. A bromine-doped sodium vanadium fluorophosphate@carbon composite material, characterized in that, It is prepared by the preparation method according to any one of claims 1-7.

9. The bromine-doped sodium vanadium fluorophosphate@carbon composite material according to claim 8, characterized in that, The particle size of the bromine-doped sodium vanadium fluorophosphate@carbon composite material is 30-50 nm.

10. The application of the bromine-doped sodium vanadium fluoride phosphate@carbon composite material as a cathode material in the preparation of sodium-ion batteries, as described in claim 8 or 9.